2009
DOI: 10.1080/10573560802683622
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Reading Fluency to Struggling Readers: Method, Materials, and Evidence

Abstract: Reading fluency has been identified as a key component in reading and in learning to read. Moreover, a significantly large number of students who experience difficulty in reading manifest difficulties in reading fluency that appear to contribute to their overall struggles in reading. In this article we explore the nature of effective instruction in fluency. We examine proven methods for teaching fluency as well as instructional routines that combine various methods into synergistic lessons. We also take issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 7 publications
3
40
0
Order By: Relevance
“…The literature supports the view that the relationship between listening and reading comprehen- sion increases with advancing school grade, as a result of the mastering of decoding skills (Hudson, Pullen, Lane, & Orgesen, 2009;Rasinski, Homan, & Biggs, 2009). Additionally, according to the model of the Simple View of Reading and the research review of Aarnoutse, Brand-Gruwel and Oduber (1997), it would be expected that correlations between the TLC-n and TLC-e forms and reading comprehension assessments would be stronger.…”
Section: Discussionmentioning
confidence: 48%
“…The literature supports the view that the relationship between listening and reading comprehen- sion increases with advancing school grade, as a result of the mastering of decoding skills (Hudson, Pullen, Lane, & Orgesen, 2009;Rasinski, Homan, & Biggs, 2009). Additionally, according to the model of the Simple View of Reading and the research review of Aarnoutse, Brand-Gruwel and Oduber (1997), it would be expected that correlations between the TLC-n and TLC-e forms and reading comprehension assessments would be stronger.…”
Section: Discussionmentioning
confidence: 48%
“…Teacher explanations, think alouds, and modeling are recognized as integral components of effective instruction for word recognition, fluency, vocabulary, and comprehension, (Coyne et al, 2009;Ehri, Satlow, & Gaskins, 2009;Rasinski, Homan, & Biggs, 2009). Therefore, it makes instructional sense that effective writing instruction would include these components of effective instruction.…”
Section: Make Teacher Explanations Think Alouds and Modeling A Consmentioning
confidence: 99%
“…Results indicated that students with LD are passively learning in large group settings with little to no specialized, intensive, and explicit instruction. Furthermore, many teachers believe students will naturally acquire fluent reading behaviors through sustained silent reading; however, struggling readers require direct instruction in reading fluency in order to make gains in fluency and comprehension (Rasinski, Homan, & Biggs, 2009). …”
mentioning
confidence: 99%